The Effectiveness of Writing Therapy on Anxiety and Depression in Patients with Leukemia - Hussam Mohammed Wafqan; Entsar Hachim Muhammad; Yasir S. Alnassar; Thabia Abdul Razak; Murtadha Hassan Ali; Mahmood Jamal Abdulhasa (International Journal of Body, Mind and Culture, 2023)
Background: The diagnosis of cancer, followed by lengthy treatment, poses a significant threat to patients' mental health. The current study aimed to examine the effectiveness of writing therapy on depression and anxiety of patients with leukemia.